TULARAEMIA − TWO CASE REPORTS IN CHILDREN - Karmen Tašner; Aneta Nikolova; Aleksandra Zorko - Brodnik; Vojko Berce (The Society for Children with Metabolic Disorders, 2020)
Tularaemia is a zoonosis, which is rare in children but should be considered in the differential diagnosis of lymphadenitis or unexplained fever, especially when epidemiological risk factors are present. In the review article, we present the characteristics of the disease, followed by two case reports in children. Signs and symptoms of different clinical forms of tularaemia are described. We also present the differential diagnosis, basic diagnostic investigations, and therapy.